Fabrication and In vitro Evaluation of Chitosan-based Nanocomposites through Ionic Gelation Method for the Sustained Release Drug Delivery of Nicorandil - Ahmed, Fahad; Mustafa, Muhammad Abid; Tayyab, Muhammad; Sarwer, Muhammad Umer; Khan, Hafeez Ullah; Zaheer, Laiba (Asian journal of pharmaceutical research and health care, 2023)
ABSTRACT Background: In this ever-evolving present era, the field of medicine is also changing and innovating at an unmatchable pace. The implication of nanotechnology in medicine is the need of the hour to serve the human health-care sector and to make this world a better place to live. In this era, humans are suffering from immense mortality because of many life-threatening diseases. Cardiovascular complications are among one of the major reasons for morbidity and mortality, such as angina pectoris. Aims and Objective: Furthermore, in the past few decades, polysaccharides such as chitosan have gained great attention to be used as a carrier system in nanomedicine due to their favorable properties. Materials with a nanoscale structure, or nanocomposites, are used to enhance products' macroscopic characteristics. A rapidly expanding field of study is nanocomposite organic/inorganic materials in general. The ability to achieve control of the nanoscale structures via novel synthetic techniques is the subject of intense research. Material and Method: Intending to formulate a sustained release nanocarrier system of an antianginal agent, i.e., nicorandil, this study has implied a widely acceptable and feasible technique of ionic gelation. This technique implies sodium tripolyphosphate having a negative charge while the cationic character of chitosan, hence resulting in the formation of a nanoscale drug carrier vehicle. Then, formulated nanocomposites were characterized by several widely accepted methods such as zeta size and potential, powder X-ray diffraction, scanning electron microscopy, FTIR, and differential scanning calorimetry and thermogravimetric analysis. Results: The mean diameter of the resulting formulation is also in the favorable range (278 nm). The formulation showed significant incorporation of active drugs inside the carrier system. Loading of drug and entrapment efficiency results were promising, while the drug release profile showed sustained drug release patterns from the vehicle. Conclusion: Thus, the present study presents the potential to overcome limitations such as low bioavailability, side effects, and poor stability of the medicinal agent used.